Chlorogenic acid and caffeine content of fermented robusta bean - TJAHJADI PURWOKO; SURANTO SURANTO; RATNA SETYANINGSIH; SOERYA DEWI MARLIYANA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Purwoko T, Suranto, Setyaningsih R, Marliyana SD. 2021. Chlorogenic acid and caffeine content of fermented robusta bean. Biodiversitas 23: 902-906. Robusta beans contain caffeine and chlorogenic acid higher than arabica beans, however, it has a lower economic value than arabica beans. Therefore, microorganisms in the robusta bean for the fermentation process are expected to reduce caffeine and chlorogenic acid contents. The objective of this research was to investigate the ability of fungus Rhizopus oryzae, yeast Saccharomyces cerevisiae, and bacteria Lactobacillus casei and Leuconostoc mesenteroides in degrading caffeine and chlorogenic acid content of robusta beans. Analysis of caffeine and chlorogenic acid content was carried out by spectrophotometer at OD275 and OD324, respectively. The caffeine and chlorogenic acid content of unfermented robusta beans were 18.64 mg/g and 62.18 mg/g. Saccharomyces cerevisiae, L. mesenteroides, L. casei, and R. oryzae were able to degrade caffeine, and reduce the caffeine content of fermented robusta beans to 16.92, 16.71, 16.67, and 13.57 mg/g, respectively. The decrease of caffeine by S. cerevisiae, L. mesenteroides and L. casei were not significantly different (p>0.05) from control, however, the decrease of caffeine by R. oryzae was significant (p<0.05). Saccharomyces cerevisiae, R. oryzae, L. mesenteroide, and L. casei were able to degrade chlorogenic acid and reduce the chlorogenic acid content of fermented robusta beans to 44.54, 45.21, 45.79, and 47.31 mg/g. Chlorogenic acid was reduced significantly by S. cerevisiae, R. oryzae, L. mesenteroides, and L. casei (p<0.05). It can be concluded that R. oryzae was a potential microorganism to reduce caffeine and chlorogenic acid contents in robusta beans.